First language influences on multilingual lexicons - Booth, Paul 1981-; Clenton, Jon (Routledge, 2020)
Introduction: 1. First language influences on multilingual lexicons: pulling apart the threads / Jon Clenton & Paul Booth -- Part I. Recognition, comprehension, and reading: 2. The Pseudohomophone Effect in visual word recognition in a Second Language / Nan Jiang & Hye Pae -- 3. L1- L2 semantic and syntactic processing: the influence of language proximity / Paul Booth, Jon Clenton & Jo Van Herwegen -- 4. The effect of Arabic word structure and L1 reading processes on the structure of the English L2 / Jim Milton & Khaled Alhazmi -- Part II. Production, translation and writing: 5. The Multilingual Lexicon: Evidence from Primed Translation Lexical Decision and Verbal Fluency Tasks / Agnieszka Ewa Krautz (Tytus) -- 6. Beyond literal: expanding vocabulary for translation skills in the diverse, multilingual undergraduate MFL classroom / Rosa Rodriguez-Garrido & Albert Pellicer -- 7. Processing L2 vocabulary in writing / Katja Mäntylä, Sinikka Lihtinen & Outi Toropainen -- 8. Use of Collocations in Written Text: a comparative analysis of collocations produced by Native Speakers and Nigerian Learners of English / Peter Obukadeta -- Part III. Vocabulary assessment: 9. First and second language cognate effects in third language vocabulary knowledge / Christina Lindqvist --10. The Reassessment of Vocabulary Tests Based on Cognate Distribution / Csaba Zoltan Szabo -- Conclusion: 11. First language influences on multilingual lexicons: drawing the threads together / Paul Booth & Jon Clenton -- Index
Includes bibliographical references and index
Keywords: Second language acquisition / Case studies; Interference (Linguistics)